An Endovascular-First Approach to the Treatment of Critical Limb Ischemia Results in Superior Limb Salvage Rates. (August 2015) - Katib, Nedal; Thomas, Shannon D.; Lennox, Andrew F.; Yang, Jia-Lin; Varcoe, Ramon L.
Purpose: To evaluate the effect of a shift to a primary endovascular revascularization (ER) strategy for patients presenting with critical limb ischemia (CLI) after a change in staff at our center in 2008 altered our revascularization strategy.Methods: Between 2004 and 2012, 344 critically ischemic limbs were treated in 279 patients (mean age 74.0±11.4 years; 179 men) during 546 separate hospital admissions. Limbs were analyzed according to (1) their principal revascularization strategy and (2) their date of presentation [early (2004–2008) or late (2008–2012)].Results: Compared with the open revascularization (OR) and no revascularization (NR) groups, the ER group had an increased freedom from major amputation (92.3% vs 80.0% OR vs 69.3% NR, p<0.001), reduced hospital stay (15.2 vs OR 31.6 vs NR 25.9 days, p<0.001), intensive care unit (ICU) stay (2.3 vs OR 23.7 vs NR 7.2 hours, p=0.033), and operating time for ER vs OR (157.9 vs 316.8 minutes, respectively; p<0.0001). There was also a significant decrease in limbs requiring minor amputations (23.2% vs OR 29.3% vs NR 37.6%, p=0.041) and mean number of admissions/limb compared to OR (1.5 vs OR 1.9 vs NR 1.5, p=0.007). The late era saw the treatment of a larger number of limbs (223 vs 121) compared with the earlier time period. This institutional shift resulted in increased freedom from major amputation (87.4% vs 74.4%, p<0.01), reduced ICU stay (3.45 vs 16.98 hours, p<0.01), and shorter length of stay (20.9 vs 31.5 days, p<0.01) between the 2 eras, respectively.Conclusion: A shift to an endovascular-first treatment strategy is associated with fewer major amputations and shorter length of stay.